Peran Motivasi Sebagai Pemediasi Pengaruh Kompensasi, Self Efficacy Terhadap Kinerja Pegawai - Husni Azahiroh; Vivin Maharani Ekowati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to examine and analyze the role of motivation as a mediator in the influence of compensation and self-efficacy on employee performance. The research was conducted at the Secretariat of The Regional House of Representatives of Malang Regency using explanatory research design and quantitative approach methods. The study population consisted of 86 people with sample selection using a saturated sampling technique. Data were obtained through interviews, literature studies, and questionnaires distributed to respondents. Data analysis was carried out using SmartPLS 4.1 with several testing stages including outer model test, inner model test, hypothesis testing, and mediation testing. The results showed that: 1) positively and significantly compensation affects employee performance with a p-value of 0.002, 2) positively and significantly self efficacy affects employee performance with a p-value of 0.010, 3) positively and significantly motivation affects employee performance with a p-value of 0.000, 4) motivation has a mediating role on the effect of compensation on employee performance with a p-value of 0.009, and 5) motivation has a mediating role on the influence between self 5) motivation has a mediating role on the effect of self efficacy on employee performance with a p-value of 0.007.